JAK inhibitors in difficult-to-treat adult-onset Still's disease and systemic-onset juvenile idiopathic arthritis. (3rd August 2022) - Gillard, Louise; Pouchot, Jacques; Cohen-Aubart, Fleur; Koné-Paut, Isabelle; Mouterde, Gaël; Michaud, Martin; Reumaux, Héloïse; Savey, Léa; Belot, Alexandre; Fautrel, Bruno; Mitrovic, Stéphane
Abstract: Objectives: Excessive and inappropriate production of pro-inflammatory cytokines plays a key role in Still's disease. Janus kinase inhibitor (JAKi) agents mainly block pro-inflammatory cytokine pathways, notably IL-6 and IFN. The objective was to assess the efficacy and safety of JAKi agents in difficult-to-treat systemic JIA or adult-onset Still's disease (AOSD). Methods: This retrospective study was based on a national survey conducted in the departments of rheumatology, paediatric rheumatology and internal medicine of French hospitals regarding systemic JIA and AOSD patients who received JAKi agents. The data were collected with a standardized questionnaire and analysed at different times (treatment initiation, months 1, 3 and 6 and the end of follow-up). Results: Nine patients (seven adults) were included. All patients showed inadequate response to CS or conventional synthetic or biologic DMARDs. Baricitinib was used in five patients, ruxolitinib in two, tofacitinib in two and upadacitinib in one. A JAKi was used combined with CS in all but two patients. A JAKi was associated with anakinra and CS in one patient, and with MTX, anakinra and CS in another. The median (range) follow-up was 16 (1–33) months. Two cases out of nine showed complete remission, 3/9 partial response and 4/9 treatment failure. At the last visit, CS could be decreased but not stopped. Tolerance of the JAKi was acceptable (no severe adverse events). Conclusion: JAKi agents may be a therapeutic option for some patients with difficult-to-treat Still's disease, especially those with partial response to medium- or high-dose CS or biologics.